Effectiveness of Biofilmed Biofertilizer with Balanced Phosphate Fertilizer Dosage in Suppressing Purple Blotch Disease Intensity and Increasing Garlic Yield on Andisol Soil in Tawangmangu - Mohammad Fikri Halim Madjid; Hadiwiyono Hadiwiyono; Sudadi Sudadi; Susilo Hamberg Poromarto (Journal of Biodiversity and Biotechnology, 2025)
Garlic productivity in Indonesia is often constrained by purple blotch disease (Alternaria porri) . A sustainable control alternative involves utilizing biofilmed biofertilizer (BiO2) combined with phosphate (P) fertilizer . This study aimed to assess the effectiveness of balancing BiO2 and P dosage in suppressing purple blotch disease intensity and increasing garlic yield on Andisol soil in Tawangmangu . The research was conducted from May to September 2024 using a single-factor Completely Randomized Design (CRD) with four treatments: P0 (0% P + 100% NK + BiO2), P1 (50% P + 100% NK + BiO2), P2 (100% P + 100% NK + BiO2), and P3 (100% NPK without BiO2) . Data were analyzed using ANOVA followed by DMRT at a 95% significance level . Results indicated that combining BiO2 with P fertilizer was highly effective; it suppressed leaf spot disease intensity by 49.47% and increased garlic yields by 20.91% compared to the control . This confirms that integrating BiO2 with appropriate P fertilization is a viable strategy for improving garlic productivity in Andisol soil .